The effects of three different exercise modalities on markers of male reproduction in healthy subjects: a randomized controlled trial. Issue 2 (February 2017) - Hajizadeh Maleki, Behzad; Tartibian, Bakhtyar; Chehrazi, Mohammad
Abstract : The aim of this study was to investigate the effects of moderate-intensity continuous training (MICT), high-intensity continuous training (HICT) and high-intensity interval training (HIIT) on markers of male reproduction including seminal markers of oxidative stress and inflammation as well as semen quality and sperm DNA integrity in healthy human subjects. A total of 397 healthy male volunteers were screened and 280 were randomly assigned to one of the MICT ( n  = 70), HICT ( n  = 70), HIIT ( n  = 70) and non-exercise (NON-EX, n  = 70) groups. Subjects had inflammatory markers (IL-1β, IL-6, IL-8 and TNF-α), oxidants (ROS, MDA and 8-isoprostane), antioxidants (SOD, catalase and TAC), semen parameters and sperm DNA damage measured at baseline (T1 ), the end of week 12 (T2 ), the end of week 24 (T3 ), and 7 (T4 ) and 30 days (T5 ) after training. Chronic MICT, HICT and HIIT attenuated seminal markers of oxidative stress and inflammation with different kinetics for the three types of exercise ( P  < 0.05), and these changes were correlated with favorable improvements in semen quality parameters and sperm DNA integrity ( P  < 0.05). MICT was superior to HICT and HIIT in the improvements of markers of male reproductive function ( P  < 0.05). In conclusion, different exercise modalities favorably affect markers of male reproduction with different kinetics, suggesting intensity-, duration- and type-dependent adaptations to exercise training in healthy human subjects.